A Preparation of Kininogen for the Assay of Kallikreins - Małofiejew, M; Buluk, K; Czokało, Maria (Thrombosis and Haemostasis, 1966)
A method by which a kininogen preparation free of kallikrein and freed of inhibitors of the kininogenic system is described. The preparation can be used for the quantitative estimation of plasma or salivary kallikrein in the presence of active factors of the fibrinolytic system, since in such a preparation freed of kallikreinogen neither the plasminogen activator nor active plasmin can form plasma kinins.